2001
DOI: 10.1007/s002440010210
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides in Water, Sediment, Crops, and Human Fluids in a Farming Community in Ghana

Abstract: A total of 208 samples of water, sediment, tomato crops, blood, and mothers' breast milk were collected from the environs of Akumadan, a prominent vegetable-farming community in Ghana. The samples were analyzed for organochlorine (OC) pesticide residues. Lindane and endosulfan were found in water and sediment, while other OC pesticide residues, such as hexachlorobenzene (HCB), p,p'-DDE, and heptachlor epoxide, were additionally found in sediment. Heptachlor epoxide was the only OC residue detected in appreciab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 9 publications
7
90
2
4
Order By: Relevance
“…In case of monocrotophos; slightly high level 0.025 -50 mg / g by Musshoff et al (2002) 0.27 mg / ml by Kocan et al (1994), 0.9 mg / L by Guardino et al (1996), 4.71 mg / L and 38.13 mg / L by Dua et al (1996), 1.9 ppb by Luo et al (1997), 0.78 mg / kg by Waliszewski et al (2000) was reported in the blood samples. Low level of DDT 0.22 mg / L, 0.25 mg / L and 0.30 mg / L was also reported by Heudorf et al (2003) Guardina et al (1996), 9.10 mg / ml by Rubin et al (2001) and 380 mg / kg by Ntow et al (2001) was reported in the exposed persons. Residues of DDE were also detected such as 5.2, 6.2 and 2.5 ng / g by Ahmed et al (2002), 3.99 mg / ml and 1.42 mg / ml by Butler et al (2003).…”
Section: Pesticide Residues In Human Bloodsupporting
confidence: 69%
“…In case of monocrotophos; slightly high level 0.025 -50 mg / g by Musshoff et al (2002) 0.27 mg / ml by Kocan et al (1994), 0.9 mg / L by Guardino et al (1996), 4.71 mg / L and 38.13 mg / L by Dua et al (1996), 1.9 ppb by Luo et al (1997), 0.78 mg / kg by Waliszewski et al (2000) was reported in the blood samples. Low level of DDT 0.22 mg / L, 0.25 mg / L and 0.30 mg / L was also reported by Heudorf et al (2003) Guardina et al (1996), 9.10 mg / ml by Rubin et al (2001) and 380 mg / kg by Ntow et al (2001) was reported in the exposed persons. Residues of DDE were also detected such as 5.2, 6.2 and 2.5 ng / g by Ahmed et al (2002), 3.99 mg / ml and 1.42 mg / ml by Butler et al (2003).…”
Section: Pesticide Residues In Human Bloodsupporting
confidence: 69%
“…Of the vegetables cultivated, tomatoes alone constitute over 90%. The tomato season runs throughout the whole year (Ntow 2001). At Akumadan, a wide and changing array of pesticides is utilized in the cultivation of vegetables.…”
Section: Methodsmentioning
confidence: 99%
“…OCPs have been used in Ghana for over 40 years, both for agricultural and public health purposes, with their residues been detected in water, sediments, vegetable crops, fish and in humans [10]. Although the production and use of many types of OCPs have been severely limited in many countries including Ghana, they are nevertheless still being used unofficially in large quantities in many parts of Ghana [11], and in other developing countries because of their effectiveness as pesticides and their relatively low cost [12] as well as inadequate regulation and management on the production, trade and use of these chemicals [13].…”
Section: Introductionmentioning
confidence: 99%